Pre-independence Chinese drama in Kuala Lumpur with special reference to Yan Keng benevolent dramatic association - Chong, Shea Tieng (2017)
In the beginning of 20th century, due to the huge population of Chinese in Kuala Lumpur, it has then became the significant place for Chinese cultural activities, especially Cantonese opera. Since the New Culture Movement influence has spread to Malaya, it has inspired the local intellectuals. Besides that, the vernacular drama has quietly sprouted and quickly developed. Yang Keng Benevolent Dramatic Association was the cultural association among the commoners. It has witnessed and participated in the development of the Chinese drama in Kuala Lumpur during that surging era. On top of the responsibility of Yan Keng Benevolent Dramatic Association to promote both traditional drama and vernacular drama, it also played its role as a charitable organisation in the society. It was not only the cream of the drama sphere but also a rare organisation that was willing to work with other organisation. This research has done an in-depth discussion about the Chinese drama activities that took place before the independence of Kuala Lumpur. It used Yan Keng Benevolent Dramatic Association as the focus of the research to analyse its vernacular drama’s repertoires, themes, screenings, objectives, theatres, scripts, writers and their charity events. There are three objectives of this research: Firstly, it fills in the gap of Kuala Lumpur drama history and enriches the research of Malaya drama; secondly, it was the first research that sorts and reconstructs the history of Yan Keng Benevolent Dramatic Association and pieces the image of common people’s activities in early days of Kuala Lumpur; thirdly, it does not only reflects the entertainment charity organisation’s value and purpose among the Malaya- Singapore Chinese society history, but also offers a new possibility of research perspective.